Creating Intelligent Pipeline for Telecom Operators Based on Flow Operation - Kefei Liu (Dianxin kexue)
After restructuring of telecom operators,with market competition increasingly fierce,price war endless,the value of telecommunications continuing to fall,telecommunications operators begin transition from voice operation to flow operation.The paper pointed out flow operation is the key to competitive game and improving the value of the operators.It's imperative to promote the flow by intelligent pipeline business development.Finally,the paper proposed to strengthen the construction of basic transmission facilities,forge flow analysis and operational capabilities for customers' needs,innovate business models and so on to create intelligent pipeline for telecom operators based on flow operation.